Dual Self‐Healing Anticorrosion Coatings Based on Multibranched Waterborne Polyurethane and TiO2 Nanocapsule‐Loaded Graphene Oxide. Issue 9 (3rd February 2022) - Zhou, Jianlin; Liu, Han; Sun, Yangyi; Chen, Kunlin
Abstract: The study reports the successful fabrication of a novel dual self‐healing anticorrosion coating based on benzotriazole loaded TiO2 nanocapsule (BTC) modified graphene oxide sheets and the multibranched waterborne polyurethane (WPU). When corrosion occurs, the benzotriazole (BZT) in nanocapsules can be slowly released from the coating forming a passivation layer on the metal surface to isolate the corrosive mediums. The anticorrosion performance of coating is examined by performing electrochemical tests. As indicated from the results, after being immersed in 3.5 wt% NaCl for 7 d, the prepared coating shows excellent anticorrosion performance with inhibition efficiency of 99%. In addition, the φ in 10 4  Hz increases from 10° to 30°, and Log| Z |0.01Hz  remains at nearly 4.5 with the immersing time extended to 30 d. Moreover, when the coating is physically damaged, the damaged coating can be self‐repaired by the reversible disulfide bonds in WPU and the releasing of the BZT simultaneously. Compared with other control anticorrosion coatings, the healed coating achieves significantly improved anticorrosion performance, and the damaged coating can still sustain the original anticorrosion performance after self‐healing. This study proposes a novel fabrication strategy for self‐healing materials, and it can contribute to the long‐term use of anticorrosion coatings. Abstract : A novel dual self‐healing anticorrosion coating based on benzotriazole loaded TiO2 nanocapsules modified graphene oxide sheets and the multibranched waterborne polyurethane is fabricated, presenting a new strategy for long‐term corrosion protection.